Dari Musibah ke Ketahanan Sosial: Analisis Sosiologi Al-Qur’an terhadap Praktik Muamalat Masyarakat Aceh Tamiang Pasca Banjir Bandang - Muhammad Roni; Mariadi Mariadi; Muhammad Nuh Rasyid (IAIN Langsa, 2025)
This study aims to examine how Quranic values are constructed and actualized within post-disaster muamalah practices and to analyze their role in fostering social resilience. This research employs a qualitative field-based approach using the perspective of Quranic sociology, drawing on observation, in-depth interviews, and thematic analysis of socio-economic practices within the community. The findings reveal that values such as taawun (mutual assistance), al-adl (justice), and ukhuwwah ijtimaiyyah (social fraternity) not only persist but are transformed into adaptive social mechanisms that support economic reconstruction and social cohesion in the aftermath of disaster. Quran-based muamalah practices thus function as a moral and social foundation for building contextual and sustainable community resilience.